The Influence of Online Customer Reviews and Online Customer Ratings on Purchase Decisions on Shopee E-Commerce in Depok - Naomi Ramadhia Amir; Alfi Maghfuriyah; Noviyanti Noviyanti (International Publisher (YAPENBI), 2026)
This study aims to analyze the influence of Online Customer Review and Online Customer Rating on Purchase Decisions on the Shopee e-commerce platform, both individually and simultaneously. The research employs a quantitative approach with a questionnaire as the primary instrument, measured using a Likert scale. Data were collected through questionnaires distributed to 140 Shopee e-commerce consumers in Depok City as the sample. The collected data were subsequently processed using multiple linear regression analysis. The sampling method applied was Non-Probability Sampling with purposive sampling and Malhotra techniques, adjusted to the criteria of respondents who had previously made purchases on Shopee and considered the review and rating features in their decision-making process. Data analysis was conducted using SPSS version 27. The study’s findings indicate that the Online Customer Review variable (X₁) has significant effect on Purchase Decisions (Y), and the Online Customer Rating variable (X₂) also exerts a significant effect on Purchase Decisions. The results of the simultaneous test demonstrate that both variables collectively have a significant influence on Purchase Decisions on the Shopee e-commerce platform. Based on the coefficient of determination test, the R Square value is 0.260 and the Adjusted R Square value is 0.249, meaning that 24.9% of the variation in Purchase Decisions can be explained by Online Customer Review and Online Customer Rating, while the remaining 75.1% is influenced by other factors such as promotion, price, brand reputation, discounts, service quality, and consumers’ personal preferences.